Pengaruh Asam Itakonat terhadap Properti Polimer Perekat Akrilik Berbasis Air: Effect of Itaconic Acid on the Properties of Acrylic Water Base Adhesive Polymer - Rony Pasonang Sihombing; Agustinus Ngatin (KOVALEN: Jurnal Riset Kimia, 2021)
Acrylic-based polymer adhesive is a type of adhesive that can be used for pressure sensitive adhesive (PSA). Itaconic acid (IA) is a type of acid with 2 (two) OH groups which can form hydrogen bonds. The acrylic base can be used purely from its class. In some cases, however, the acrylic base can be used together with another base. Therefore acrylic-based adhesive with variable addition of itaconic acid was introduced in this study. In this application, the holding power property is one of the important parameters of a PSA. Therefore, holding power is the main parameter in this study. This research includes the preparation of tools and materials, mixing the main raw materials of acrylic monomer and itaconic acid with the types of surfactants and water, and product characterization. The polymerization process is carried out at a pressure of 1 atm with a temperature of 75°C - 80°C accompanied by stirring with a rotation rate of ± 500 rpm. The characterization of this research resulted in a PSA product with a holding power of 2 kg for 30 seconds to 620 minutes. While the resulting peel strength is 1.12 kgf / inc to 0.76 kgf / inc. Keywords: itaconic acid, acrylic PSA, holding power